An Inclusive Approach of Urban Open Space Analysis via Field Sketching - Benkaid Kasbah, Seloua; Eplényi, Anna (Landscape Architecture and Art, 2023)
This research explores how field sketch drawing can help in understanding, and analysing urban open spaces, and their potential roles for their experiential dimension. The research begins with a theoretical interpretation of the term “Place” and an examination of the components that make up an urban open space. This is followed by an analytical study of field sketch drawing techniques, which are selected and applied to develop an inclusive approach for analysing urban open spaces via field sketching. The final product of this research includes a theoretical study of urban space components and field sketching, serving as a comprehensive guide for analysing urban spaces through field sketching. The research findings highlight the potential of field sketch drawing as a valuable method for understanding and analysing urban open spaces, and its ability to enhance the experiential dimension of these spaces. The proposed inclusive field sketching approach provides a practical tool for designers and planners to conduct on-site analysis and generate preliminary design proposals for urban open spaces. The results of this research contribute to the field landscape architecture and design by providing insights and recommendations for incorporating field sketching as a valuable approach in the analysis and design of urban open spaces.